VENTILATOR-ACQUIRED PNEUMONIA: STRATEGIES FOR PREVENTION, DIAGNOSIS, AND TREATMENT - Dr. V. C. Patil, Dr. Archana Rokade, Dr. U.T.Mane (Obstetrics and Gynaecology Forum, 2024)
Ventilator-acquired pneumonia (VAP) remains a significant challenge in intensive care units (ICUs), contributing to increased morbidity, mortality, and healthcare costs. This research paper provides a comprehensive review of current strategies for the prevention, diagnosis, and treatment of VAP. Key preventive measures include hand hygiene, oral care, elevation of the head of the bed, subglottic suctioning, and selective decontamination of the digestive tract. Prompt diagnosis relies on clinical assessment, chest X-rays, and microbiological cultures of respiratory secretions. Empirical antibiotic therapy targeting common pathogens is crucial, with de-escalation based on culture and susceptibility results. Adjunctive therapies and supportive care play essential roles in optimizing patient outcomes.